The Influence Of Products Quality And Promotions On Purchase Decisions In Marketplace Shopee (Case Study: Students Telkom University) - Mendrofa, Clara Forendza; Rachmawati, Indira (eProceedings of Management, 2023)
The purpose of this study was to determine whether Product Quality (X1) and Promotion (X2) had an effect onPurchase Decisions (Y) on Telkom University Students. The phenomena in this study were explored usingquantitative methods. Researchers distributed questionnaires to Telkom University students with a total of 395respondents. Data analysis used descriptive analysis techniques, classical assumption test, and multipleregression analysis to answer the proposed hypothesis. The results showed that partially Product Quality (X1)and Promotion (X2) variables had a significant effect on purchasing decision making (Y) for Telkom Universitystudents in the Shopee Marketplace. The three variables of Product Quality (X1) and Promotion (X2) also have asignificant simultaneous effect on the Purchase Decision (Y) of Telkom University students in the ShopeeMarketplace.Keywords-products quality, promotion, and purchase decision